Bioactivity-Guided Extraction and Identification of Antibacterial Compound from Marine Actinomycetes Strains Isolated from Costal Soil Samples of Rameswaram and Dhanushkodi, Tamil Nadu, India - Kannabiran, Dr. Krishnan (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To isolate and identify marine actinomycetes with potential antibacterial activity. Materials and Methods: Marine actinomycetes were isolated from soil samples collected at the Rameswaram and Dhanushkodi coast of Tamil Nadu, India. The isolated strains were screened for antibacterial activity by cross-streaking method against Escherichia coli and Bacillus cereus. Actinomycetes isolates demonstrated potential antibacterial activity were mass cultured and secondary metabolites were extracted using chloroform. The crude extract prepared was analyzed for antibacterial activity by well diffusion method (100 Î¼g/0.1 ml) and also subjected to chemical characterization using gas chromatography-mass spectrometry (GC-MS) JEOL (GCMATE II GC-MS, Agilent Technologies 6890N Network GC system for GC). Results: Among the five different isolation media used, composed Starch Casein Agar (composed) proved to be most effective for isolation of actinomycetes from Rameswaram and Dhanushkodi coastal soil samples. Among the 100 isolated strains, 10 isolates (LGK001 to LGK010) demonstrated a significant antibacterial activity with the zone of inhibition ranging from 8 to 12 mm against Escherichia coli and B. cereus. Based on the GC-MS analysis, all 10 isolates produced either gancidin-W (and/or) cyclo-pro-phe as major secondary metabolites in their crude extracts. Both these molecules are previously reported antibiotic compounds. Conclusion: The results of this study suggest that Rameswaram and Dhanushkodi coastal soil samples are the rich sources for antibacterial bioactive compounds (gancidin-W and cyclo-pro-phe) producing actinomycetes.